The Association Study of IL-23R Polymorphisms With Cerebral Palsy in Chinese Population - Wang, Yangong; Xu, Yiran; Fan, Yangyi; Bi, Dan; Song, Juan; Xia, Lei; Shang, Qing; Gao, Chao; Zhang, Xiaoli; Zhu, Dengna; Qiao, Yimeng; Su, Yu; et al. (Frontiers in Neuroscience, 2020)
Background: Cerebral palsy (CP) is a syndrome of non-progressive motor dysfunction caused by early brain development injury. Recent evidence has shown that immunological abnormalities are associated with an increased risk of CP. Methods: We recruited 782 children with CP as the case group and 770 healthy children as the control group. The association between IL-23R single nucleotide polymorphisms (SNPs; namely, rs10889657, rs6682925, rs1884444, rs17375018, rs1004819, rs11805303, and rs10889677) and CP was studied by using a case–control method and SHEsis online software. Subgroup analysis based on complications and clinical subtypes was also carried out. Results: There were differences in the allele and genotype frequencies between CP cases and controls at the rs11805303 and rs10889677 SNPs (Pallele = 0.014 and 0.048, respectively; Pgenotype = 0.023 and 0.008, respectively), and the difference in genotype frequency of rs10889677 remained significant after Bonferroni correction (Pgenotype = 0.048). Subgroup analysis revealed a more significant association of rs10889677 with CP accompanied by global developmental delay (Pgenotype = 0.024 after correction) and neonatal encephalopathy (Pgenotype = 0.024 after correction). Conclusion: The present results showed a significant association between IL-23R and CP, suggesting that IL-23R may play a potential role in CP pathogenesis.